Lateral osteophytes do not represent a contraindication to medial unicompartmental knee arthroplasty: a 15-year follow-up - Hamilton, T; Choudhary, R; Jenkins, C; Mellon, S; Dodd, C; Murray, D; Pandit, H (Springer Berlin Heidelberg, 2016)
Purpose: Lateral osteophytes have been reported to be associated with lateral compartment disease and as such it is unclear whether medial unicompartmental knee arthroplasty should be performed if these are present. Methods: Using the OARSI classification system, 0 (no osteophyte) to 3 (large osteophyte), radiographs from a series of cemented meniscal-bearing unicompartmental knee arthroplasty implanted in the setting of full thickness lateral cartilage where lateral osteophytes were not considered a contraindication were identified and factors associated with the presence and size of lateral osteophytes, and their impact on clinical outcomes and implant survival were assessed. Results: Pre-operative radiographs from 458 knees (392 patients), independently followed-up for a mean 10.5 years (range 5.3-16.6) were assessed. Lateral osteophytes were present in 62% of knees with 18% scored as Grade 3. Inter-observer reliability was good (kappa=0.70). The presence and size of lateral osteophytes was associated with younger age at joint replacement (p=0.01) and increasing BMI (p=0.01). No association was seen with gender, pre-operative status, assessed using the Oxford Knee Score (OKS), American Knee Society (AKSS) Objective or Functional Score, and Tegner activity score, or size of medial tibial lesion. Subgroup analysis of Grade 3 Osteophytes, revealed that these were associated with a greater degree of macroscopic ACL damage. At ten years there was no difference in function, survival or mechanism of failure between groups (n.s.). Subgroup analysis of Grade 3 osteophytes, found no significant difference in functional outcome at 10 years or implant survival at 15 years. Conclusion: The presence of lateral osteophytes is not a contraindication to medial meniscalbearing unicompartmental knee arthroplasty. The clinical relevance of this study is that it highlights the importance of an appropriate preoperative assessment of the lateral compartment as in the setting of full thickness cartilage at operation lateral osteophytes do not compromise long term functional outcome or implant survival.